Socio-Economic Determinants of Stunting Prevalence Toddlers in Regencies/Cities on Lampung Province 2018-2024 - Julita .; Asih Murwiati (CV. ITTC INDONESIA, 2026)
Stunting is defined as a child's growth failure caused by long-term malnutrition, especially in the first 1,000 days of life. In 2020, Indonesia had a toddler stunting prevalence of around 31.8%, making it the second highest in Southeast Asia after Timor Leste. Indonesia's National Medium-Term Development Plan (RPJMN) sets a target of reducing stunting prevalence to 14% by 2024. This study analyzes the socio-economic determinants that influence the prevalence of toddler stunting in 15 regencies/cities in Lampung Province in 2018-2024. This study uses a quantitative descriptive approach, panel data analysis. Secondary data used comes from data from the Central Statistics Agency (BPS) of Lampung Province and the Indonesian Ministry of Health from 2018–2024. The results of this study indicate that Per Capita Expenditure (PP) has a negative and significant effect on the prevalence of toddler stunting. Average Years of Schooling for Girls (RLP) has a positive and significant effect on the prevalence of toddler stunting. Access to Proper Sanitation (SL) has a negative and significant effect on the prevalence of toddler stunting. The percentage of clean drinking water (AML) has a negative and significant effect on the prevalence of stunting in toddlers. Insufficient food consumption (KP) has a positive and significant effect on the prevalence of stunting in toddlers. This study shows that socioeconomic determinants collectively influence the dependent variable (stunting prevalence).